Inovasi Teknologi Produk Unggulan Kerajinan Cobek Selo Parang Kampung KB Desa Tulungrejo Kecamatan Ngantang Kabupaten Malang - Yazirin, Cepi; Sulo, Bambang Dwi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The lack of technology is one of the barriers for someone to be more developed than before. Science and technology today are the backbones of economic development. This is what happened in the family planning village (KB) in Tulungrejo Village, Ngantang District, Malang Regency. The low level of technology is one of the obstacles to maintaining product quality and the health of the majority of Tulungrejo villagers. The abundance of raw materials obtained directly from the mountain is not matched by this increasingly sophisticated technology, causing the production process to be underdeveloped. On the other hand, the residents of Tulungrejo Village seem to have forgotten the importance of using personal protective equipment. The production process still uses traditional equipment so that the manufacturing and marketing processes are hampered. The manufacture of cobek lathes is expected to improve quality, speed, and reduce risks to health. Because the equipment used by the majority of the KB village community in Tulungrejo village uses personal protective equipment that is not following what it should be. One of them is not wearing a mask according to national standards, so it has the potential for health because the dust generated from the mortar manufacturing process can interfere with breathing. The result is that the use of a lathe can cut production time faster than the use of a grinder that is usually used by residents to produce the mortar, the work is neater and even, the production time is faster than the use of a grinder, and in terms of K3 the use of a lathe is safer because the mortar is direct. clamped on the lathe so that it is stronger and the resulting dust can be minimized with water cooling media.